If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -6 + 4T = 3t Solving -6 + 4T = 3t Solving for variable 'T'. Move all terms containing T to the left, all other terms to the right. Add '6' to each side of the equation. -6 + 6 + 4T = 6 + 3t Combine like terms: -6 + 6 = 0 0 + 4T = 6 + 3t 4T = 6 + 3t Divide each side by '4'. T = 1.5 + 0.75t Simplifying T = 1.5 + 0.75t
| 12-(4m+7)=3+2m-16 | | -0.2(6.5n-2)=0.848 | | -3=x/12 | | (12y-y)=11 | | 4(5-2y)=2(1-y) | | 0=-3x^3-3x^2+168x | | -3-7x=-66 | | -3-7=-66 | | y=7-7x | | -12=2x-7 | | -2x-25=-5x-7 | | 50*x=109 | | 15x-4=5x+16 | | 24-3x=4x+10 | | (2x+2)+(5x+3)=90 | | (2x+2)+(5x+3)=180 | | -11r+9r=8 | | 15x-3=10x+12 | | (2x+2)=(5x+3) | | 2r+r+2=20 | | 4x^2=181 | | 10m+m-6m=5 | | 3x+x+5=13 | | (x-3)*(x+2)=0 | | 3x-4+2x-6=180 | | 2x^2-4+6=0 | | 0.3(5.5)-0.4(6-5.5)=0.9 | | 2u-10u+6u=-20 | | (6x-12)2=12 | | 0.3x-0.4(6-x)=0.9 | | -13s+3s=10 | | -3x*(5+-3)=51 |